Reslizumab versus placebo for poorly controlled, severe eosinophilic asthma: meta-analysis - Milosavljević, Miloš N.; Jankovic, Slobodan M.; Pejčić, Ana V.; Milovanović, Jasmina R.; Opančina, Valentina D.; Kostić, Marina J. (Vojnosanitetski pregled, 2020)
Background/Aim. Reslizumab is humanized monoclonal antibody produced by recombinant DNA technology which binds to circulating interleukin-5 (IL-5) and down-regulates the IL-5 signaling pathway. Reslizumab is indicated for the add-on maintenance treatment of patients 18 years and older with severe eosinophilic asthma phenotype whose symptoms were inadequately controlled with inhaled corticosteroids. The aim of this meta-analysis was to assess the efficacy and safety of reslizumab compared to placebo in patients suffering from inadequately controlled, moderate-to-severe asthma with elevated blood eosinophil counts. Methods. Our meta-analysis was based on systematic search of literature and selection of high-quality evidence according to pre-set inclusion and exclusion criteria. The effects of reslizumab and placebo were summarized using Review Manager (RevMan) 5.3.5 and heterogeneity was assessed by the Cochrane Q test and I² values. Several types of bias were assessed and publication bias shown by Funnel plot and Egger’s regression. Results. The meta-analysis included 5 randomized, placebo-controlled clinical trials. Reslizumab 3.0 mg/kg produced substantial improvements in forced expiratory volume in 1. second (FEV 1) (mean difference 0.15 [0.10, 0.21]) and in forced vital capacity (FVC) (mean difference 0.21 [0.09, 0.32]) over the 15 or 16-week treatment period, substantial decrease versus placebo in Asthma Control Questionnaire (ACQ) score (mean difference -0.28 [-0.41, -0.16]), and substantial increase vs. placebo from baseline in Asthma Quality of Life Questionnaire (AQLQ) total score (mean difference 0.24 [0.06, 0.43]). Also, reslizumab 3.0 mg/kg caused less adverse events versus placebo (OR 0.67 [0.51, 0.88]), especially asthma worsening (OR 0.53 [0.36, 0.77]) or bronchitis (OR 0.42 [0.24, 0.74]). Conclusion. On the basis of published clinical trials reslizumab could be considered as an effective and safe therapeutic option for severe, poorly controlled eosinophilic asthma for the time being.
Keywords: asthma; eosinophilia; anti-asthmatic agents; reslizumab; treatment outcome; meta-analysis as topic.